Relationship between Mother's emotional intelligence, negative parenting behaviour, Preschooler's attachment instability, and smart device overdependence - Gumhee Lee; Sungjae Kim (BMC, 2022)
Abstract Background As smart device overdependence among preschoolers could adversely affect their overall development, it is essential to understand the related factors of such overdependence. Mothers have a large influence on preschoolers; however,, the relationship between mothers' emotional intelligence, negative parenting behaviour, preschoolers' attachment instability, and smart device overdependence remain unclear. This study aims to develop and test a structural model to explain smart device overdependence among preschoolers. Methods The study collects and analyses data from January to May 2021 from 283 mothers raising children aged 3-6 years in South Korea. Questionnaires regarding mothers' emotional intelligence and negative parenting behaviour, as well as preschoolers' attachment instability and smart device overdependence, were used to collect data. The data were analysed by SPSS23.0 and AMOS 23.0 software and a structural equation model was constructed; p ≤ 0.05 was taken as significant. Results Mothers' emotional intelligence had a direct negative relationship with mothers' negative parenting behaviour (β = − 0.44) and an indirect negative relationship with preschoolers' attachment instability (β = − 0.25) and preschoolers' smart device overdependence (β = − 0.24). Mothers' negative parenting behaviour had a direct positive relationship with preschoolers' attachment instability (β = 0.56) and both direct and indirect positive relationships with preschoolers' smart device overdependence (β = 0.55). Preschoolers' attachment instability had a direct positive relationship with preschoolers's smart device overdependence (β = 0.46). Conclusions Mothers' emotional intelligence, negative parenting behaviour, and preschoolers' attachment instability are associated with preschoolers' vulnerability to smart device overdependence. These results are shown that more attention is needed to these variables in order to reduce preschoolers' overdependence on smart devices. Additionally, we propose to develop and provide interventions based on these results.